2004
DOI: 10.1177/002215540405200110
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of BMP-2/-4, FGF-4, and WNT10b in the Developing Mouse First Lower Molar

Abstract: S U M M A R YIntercellular signaling controls all steps of odontogenesis. The purpose of this work was to immunolocalize in the developing mouse molar four molecules that play major roles during odontogenesis: BMP-2, -4, FGF-4, and WNT10b. BMP-2 and BMP-4 were detected in the epithelium and mesenchyme at the bud stage. Staining for BMP-2 markedly increased at the cap stage. The relative amount of BMP-4 strongly increased from E14 to E15. At E15, BMP-4 was detected in the internal part of the enamel knot where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 48 publications
3
81
0
1
Order By: Relevance
“…Among them, BMP-2 is one of the most crucial for regulating epithelial-mesenchymal interactions and is expressed in the primary enamel knot, which is an epithelial signaling center and plays a central role in tooth morphogenesis (9,27). In tooth development, DSPP is a marker of odontoblast differentiation and is associated with dentin mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, BMP-2 is one of the most crucial for regulating epithelial-mesenchymal interactions and is expressed in the primary enamel knot, which is an epithelial signaling center and plays a central role in tooth morphogenesis (9,27). In tooth development, DSPP is a marker of odontoblast differentiation and is associated with dentin mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BMP-2 was detected at the apical and basal poles of preameloblasts in the developing mouse first lower molar [24], and, BMP-2, which induces ameloblast differentiation in vitro enamel organ culture [9]. These studies suggested that BMP-2 play a role on the ameloblasts differentiation.…”
Section: Discussionmentioning
confidence: 89%
“…Although previous studies documented several BMP subtypes (BMP2 to -7) expressed in the tooth germ (1), in particular, expression of BMP2 and BMP4 may be marked and associated with the epitheliummesenchyme interaction from the initiation stage to crown stage (1,15,17). Thus, we examined mRNA expression of BMP2 and BMP4 together with three BMP receptor subtypes (BMPR1a, 1b, and 2).…”
Section: Bmpmentioning
confidence: 99%